THE IMPACT OF CHRONIC PELVIC PAIN ON THE QUALITY OF LIFE OF PATIENTS WITH ENDOMETRIOSIS – A SYSTEMATIC REVIEW - Białek, Agnieszka Barbara; Bojarska, Wiktoria; Gilarska, Gabriela; Januszczak, Radosław; Cholewa, Julianna; Sygacz, Maja (International Journal of Innovative Technologies in Social Science, 2026)
Background: Endometriosis is a chronic gynecological condition affecting 6–10% of women of reproductive age, with chronic pelvic pain (CPP) being its most common symptom. The purpose of this article is to compile information on the impact of CPP on the quality of life (QoL) of women with endometriosis, based on the results of observational studies.Methods: The authors searched the PubMed, Google Scholar, Embase, and Scopus databases, including English-language articles published since January 2023. The following search terms were used: “chronic pelvic pain”, “endometriosis AND chronic pelvic pain”, “chronic pelvic pain AND quality of life”, “endometriosis AND quality of life”. The Newcastle-Ottawa Scale (NOS) was used to assess the quality of the studies.Results: The authors analyzed the results obtained from a literature search and identified six studies describing the findings of observational research. Although  the selected articles are characterized by heterogeneity in terms of methods and study populations, all studies suggested that the greatest clinical and psychosocial burden is associated not only with the diagnosis of endometriosis itself, but primarily with the pain component, especially when the pain is chronic.Conclusion: Given the close link between CPP and patients’ quality of life, the authors emphasize the importance of a holistic approach among physicians treating women with endometriosis.